2019
DOI: 10.3390/rs12010040
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Chlorophyll-a Algorithm for Assessing Trophic States of a Tropical Brazilian Reservoir Based on MSI/Sentinel-2 Data

Abstract: Using remote sensing for monitoring trophic states of inland waters relies on the calibration of chlorophyll-a (chl-a) bio-optical algorithms. One of the main limiting factors of calibrating those algorithms is that they cannot accurately cope with the wide chl-a concentration ranges in optically complex waters subject to different trophic states. Thus, this study proposes an optical hybrid chl-a algorithm (OHA), which is a combined framework of algorithms for specific chl-a concentration ranges. The study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 71 publications
(113 reference statements)
1
22
0
1
Order By: Relevance
“…The concentration of Chl‐a and a proxy for turbidity was estimated by applying the MSI imagery from Sentinel‐2 satellite Level 2A products, based on empirical equations that combine reflectance from different bands (Grendaitė et al, 2018; Peppa et al, 2020). The indices used in this study for parameter estimation were (B5‐B6) for Chl‐a and (B4) for turbidity (Cairo et al, 2020; Membrillo‐Abad et al, 2016; Peppa et al, 2020), where B4, B5, and B6 are the bands of reflectance at λB4=665nm, λB5=705nm, and λB6=740nm central wavelengths, respectively, (see for the analysis of the accuracy of the estimations). In the case for the Chl‐a, this index weights the height of the peak of the B5 band against the baseline of its adjacent peaks of either the B4 and/or the B6 spectral bands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of Chl‐a and a proxy for turbidity was estimated by applying the MSI imagery from Sentinel‐2 satellite Level 2A products, based on empirical equations that combine reflectance from different bands (Grendaitė et al, 2018; Peppa et al, 2020). The indices used in this study for parameter estimation were (B5‐B6) for Chl‐a and (B4) for turbidity (Cairo et al, 2020; Membrillo‐Abad et al, 2016; Peppa et al, 2020), where B4, B5, and B6 are the bands of reflectance at λB4=665nm, λB5=705nm, and λB6=740nm central wavelengths, respectively, (see for the analysis of the accuracy of the estimations). In the case for the Chl‐a, this index weights the height of the peak of the B5 band against the baseline of its adjacent peaks of either the B4 and/or the B6 spectral bands.…”
Section: Methodsmentioning
confidence: 99%
“…Because monitoring a lake is an intricate task that demands time and resources, an excellent alternative procedure for lake monitoring is the remote sensing techniques that have been developed and improved in recent years, particularly the use of satellite sensors (Cairo et al, 2020 ; Toming et al, 2016 ). Recently, satellite data has been used to monitor water quality and trophic state based on the concentration of Chl‐a, turbidity, among other parameters.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the WHO has established the value of 10 µg chl_a L −1 as the first alert level to freshwater bodies use for recreational activities [44]. In this context, many studies have demonstrated that the returned signature from oligotrophic waterbodies is different compared to that returned from mesotrophic or eutrophic waterbodies [45][46][47], meaning that sensitive spectral regions to water bodies highly laden in chl_a are not necessarily the same for water bodies moderately or poorly laden in chl_a concentrations. As a consequence, using a specific model to each trophic level could enhance the quality of chl_a estimates than using a unique model for all trophic levels [48].…”
Section: Ensemble-based Systemmentioning
confidence: 99%
“…Reservoirs are also simple targets for waste disposal [5]. The biotic and abiotic variables of these functionally complex ecosystems undergo rapid changes owing to natural environmental changes, changes in watershed land cover and land use, and changes in water demand [6]. The construction and use of reservoirs change the hydrodynamics of rivers, with different impacts on terrestrial and aquatic systems [7].…”
Section: Introductionmentioning
confidence: 99%